The first family-based breeding program in aquaculture - Trygve Gjedrem (Blackwell Publishing Asia Pty Ltd, 2025)
Individual selection for growth rate has been practised for aquatic species for many years. However, the use of a small number of breeders without records of parentage frequently results in inbreeding depression. AKVAFORSK began the first ever family-based breeding program in aquaculture in 1975 for Atlantic salmon in Norway. The first steps of the program involved estimating the phenotypic and genetic parameters of economically important traits and generating a base population by crossing wild salmon strains. As information on quantitative genetics for salmon was not available, the breeding program started by selecting for body weight. As information was gathered, other traits such as age at sexual maturation, disease resistance and product quality were added to the selection index. The salmon industry was invited to participate in the breeding program, which has been managed by Aqua Gen AS since 1993. The genetic gain achieved has been estimated at approximately 14% per generation with a global benefit ⁄ cost ratio estimated at 15 ⁄ 1.